Deskripsi Sanitasi Sarana PembuanganTinja Di Desa Jebeng palmitan Kecamatan Sukoharjo Kabupaten Wonosobo Tahun 2017 - Syafiah Rifa Adina; Suparmin Suparmin (Buletin Keslingmas, 2018)
AbstractDescription Sanitation of Excreta Disposal Facility in Jebengplampitan Village, sub district of Sukoharjo,WonosoboRegency 2017.Excreta disposal facility is the important part of environment health. To preventFaecal Borne Diseases disruption and spreading, feces need to handle sanitarily. Depend on the previousstudy found out that the sanitation of excreta disposal facility in Jebengplampitan Village, sub district ofSukoharjo, WonosoboRegency still low, from 228 KK (100%) there are 20 KK (8,8%) has up to standardtoilet, there is water seal latrine. Whereas 208 KK (91,2%) has below standard toilet. The purpose of thisresearch is to know the sanitation of excreta disposal facility in Jebengplampitan Village, sub district ofSukoharjo, WonosoboRegency in the year 2017.The kind of this research is descriptive research. Samplingtaken by random sampling. The collecting data methods are observation and interview by using checklist andquestioner. The subject of this research is excreta disposal facility that used by society in JebengplampitanVillage, sub district of Sukoharjo, WonosoboRegency.The result of this research point out that the sanitationcondition of excreta disposal facilityin Jebengplampitan Village, sub district of Sukoharjo, WonosoboRegencyfrom 47, there are 42 (89,4%) fulfill standard, 5 (10,26%) below of standard. By this result toilets there are45 (95,7%) without septictank, whereas 2 (4,3%) toilet with septictank.This research can be conclude that thesanitation condition of excreta disposal facilityin Jebengplampitan Village, sub district of Sukoharjo, WonosoboRegency are below of standard from 47 houses, only 2 houses that have fulfill standard toilet, andthe other dumping into the fish pool or river. The writer propose in order to the family that has no septictank,should be built quickly, health society center (Puskesmas) preferable to doing Health promotion in everyfamily and the society make it joint budgeting into building excreta disposal facility.